Imagining Earth Concepts of Wholeness in Cultural Constructions of Our Home Planet - Nitzke, Solvejg; Pethes, Nicolas (Edition Kulturwissenschaft, 2017)
While concepts of Earth have a rich tradition, more recent examples show a distinct quality: Though ideas of wholeness might still be related to mythical, religious, or utopian visions of the past, ''Earth'' itself has become available as a whole. This raises several questions: How are the notions of one Earth or our Planet imagined and distributed? What is the role of cultural imagination and practices of signification in the imagination of ''the Earth''? Which theoretical models can be used or need to be developed to describe processes of imagining Planet Earth? This collection invites a wide range of perspectives from different fields of the Humanities to explore the means of imagining Earth.